2006
DOI: 10.1080/10245330500322321
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 expression in acute leukemia

Abstract: The biological value of cyclin D1 over expression might be different in AML and ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 9 publications
(8 reference statements)
8
13
0
1
Order By: Relevance
“…In agreement with previous studies, [13,[19][20][21], we found over expression of cyclin D1 and Ki-67 in ALL patients. On the other hand, [22] we did not detect any elevation of cyclin D1 level among their ALL patient group (0/24).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with previous studies, [13,[19][20][21], we found over expression of cyclin D1 and Ki-67 in ALL patients. On the other hand, [22] we did not detect any elevation of cyclin D1 level among their ALL patient group (0/24).…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with previous results, [19][20][21]25], the frequency of cell cycle parameters (Ki-67 and cyclin D1)- positive ALL was higher in patients presenting with organomegaly and lymphadenopathy although not statistically significant. Cyclin D1 overexpression might have a role in blast mobilization from the bone marrow to lymph nodes [21] and Ki-67 expression was also related to organomegaly and extramedullary infiltration in ANLL with some reports concerning specific organ infiltrates [20,26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the current study, we showed that 1 to 5 M doses of ZnPP suppress cell proliferation in K562 and HepG2 cells in part by inhibiting cyclin D1 expression. Corroborating our findings, the overexpression of cyclin D1 is known to play a role in hepatoma and leukemia development by stimulating cell proliferation (35,36). Additionally, we showed that ZnPP significantly inhibited the expression of a number of genes critically related to cell proliferation and angiogenesis ( Table 1).…”
Section: Discussionmentioning
confidence: 64%
“…In ALL, alterations in Cyclins D1 -CCND1 [5], [6], D3 -CCND3 [7], E1 -CCNE1 [8] and A1-CCNA1 [9], Cyclin dependent kinases (CDK) 2 &6 -CDK2 & CDK6 [10], [11] [Figure 1], cyclin dependent kinase inhibitors CDKN2A, CDKN2B [12], CDKN1B [13], CDKN1C [14] have been reported. The differential expression, especially of the cyclins and the CDKs, leads to loss of checkpoint control and hence results in neoplastic transformation, which is also evident from our earlier studies [15]–[17] and hence these proteins would serve as important drug targets.…”
Section: Introductionmentioning
confidence: 99%